2010
DOI: 10.1111/j.1574-6968.2010.02172.x
|View full text |Cite
|
Sign up to set email alerts
|

Ssg, a putative glycosyltransferase, functions in lipo- and exopolysaccharide biosynthesis and cell surface-related properties in Pseudomonas alkylphenolia

Abstract: In the presence of vaporized p-cresol, Pseudomonas alkylphenolia KL28 forms specialized aerial structures (SAS). A transposon mutant of strain KL28 (C23) incapable of forming mature SAS was isolated. Genetic analysis of the C23 mutant revealed the transposon insertion in a gene (ssg) encoding a putative glycosyltransferase, which is homologous to the Pseudomonas aeruginosa PAO1 PA5001 gene. Deletion of ssg in KL28 caused the loss of lipopolysaccharide O antigen and altered the composition of the exopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 34 publications
(54 reference statements)
1
28
0
Order By: Relevance
“…Another gene related to the synthesis of the LPS core is PA5001, encoding a putative glycosyltransferase that, like wapR, is located in the LPS core biosynthesis cluster (42). PA5001 is homologous to the gene ssg (cell surface sugar biosynthetic glycosyltransferase) of Pseudomonas alkylphenolia, with 79% identity (43). By homology, the P. aeruginosa PA5001 gene is designated ssg here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another gene related to the synthesis of the LPS core is PA5001, encoding a putative glycosyltransferase that, like wapR, is located in the LPS core biosynthesis cluster (42). PA5001 is homologous to the gene ssg (cell surface sugar biosynthetic glycosyltransferase) of Pseudomonas alkylphenolia, with 79% identity (43). By homology, the P. aeruginosa PA5001 gene is designated ssg here.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, no study had previously shown a similar phenotype produced by a mutation in PA5001 in this microorganism. However, the ssg mutant of P. alkylphenolia has an LPS with a truncated core and without O antigen (43).…”
Section: Analysis Of Lps From Selected Susceptible Mutants the Polymmentioning
confidence: 99%
“…For example, the deletion of ssg, which encodes a glycosyltransferase in Pseudomonas alkylphenolia KL28, has been shown to cause the loss of lipopolysaccharide O antigen, which alters the composition of the exopolysaccharide. Furthermore, this mutant strain was found to have reduced surface spreading, reduced pellicle formation, and reduced biofilm formation; these were probably due to the cumulative effects of lipopolysaccharide truncation and alterations to the cell's exopolysaccharide composition (23). In some bacterial species, UDP-Nacetylglucosamine-1-phosphate transferase has been shown to play an important role in the biosynthesis of various polymers within the bacterial cell wall, such as common antigen and lipopolysaccharide O antigen (32).…”
Section: Resultsmentioning
confidence: 99%
“…Chromosomal DNA was isolated from the pelleted cells as described above and digested with the restriction enzyme BamHI, which does not cut within the transposon sequence of pRL27. The digested DNA was cleaned, which was followed by self-ligation using the T4 ligase at 20°C for 1 h. Material from ligated mixtures was transformed into E. coli DH5␣ pir, as previously described, and plated onto LB agarkanamycin plates in order to select for cells transformed with the ligated pRL27 plasmid that also contained the flanking P. nitroreducens TX1 DNA (23). Next, the transposon with its flanking DNA was isolated using the Midi Plus ultrapure plasmid extraction system (Viogene, Taipei, Taiwan).…”
Section: Methodsmentioning
confidence: 99%
“…A putative glycosyltransferase, PA5001, is localized in this cluster, and it might be required for the addition of Glc III (as proposed by King and coauthors [18]). Our group has recently reported that the encoded product of the ssg gene, a homologue of PA5001, in Pseudomonas alkylphenolia is a putative glycosyltransferase that is important for both LPS and exopolysaccharide biosynthesis (31). In terms of having the last outer core glucosyltransferase gene located outside the core OS biosynthesis locus, there is precedent to this observation since a gene encoding the putative 1,6-rhamnosyltransferase, MigA, is also localized outside the core cluster.…”
Section: Discussionmentioning
confidence: 99%